PENGARUH KEPEMILIKAN MANAJERIAL, LEVERAGE, DAN KEPEMILIKAN PUBLIK TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA UNTUK TAHUN 2018-2021 - Pranata, Maria Gabriela; Anggarani, Asih; Aryanindita, Gabriel P (Universitas Trilogi, 2023)
This study aims to analyze the effect of managerial ownership, leverage, and public ownership on accounting conservatism in mining companies in Indonesia for the year 2018-2021. By using purposive sampling data collection criteria, 27 companies were found. This study uses multiple linear regression analysis and uses two supporting theories, namely signaling theory and agency theory. Based on the results of analysis testing, managerial ownership has no effect on accounting conservatism. Meanwhile, leverage and public ownership have a significant positive effect on accounting conservatism. Keywords: managerial ownership; leverage; public ownership; accounting conservatism